FEEDBACK IN RHYTHMIC GYMNASTICS AS A PROCESS OF CORRECTING TECHNICAL MISTAKES - Moraru C. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
Moves in rhythmic gymnastics require a very good technique both biomechanically, esthetically and artistically speaking, thus relating this sportive field to art. That is why scoring the contest exercises is made according to the scoring code that penalizes each and every technical mistake. In order to ensure the training's quality and efficiency, technical mistakes require a special type of analysis, allowing their correct identification and their subsequent elimination from the training process. An efficient method of providing feedback about the gymnasts' mistakes is the use of video registrations, where the move's main characteristics can be noted. Therefore, our paper's goals are the video analysis of the main types of ball handling and the role of the feedback in correcting technical mistakes in rhythmic gymnastics. The batch of athletes included 4 gymnasts of the third category who participated in both contests (National Juniors' Championship and Romanian Cup) of 2010 and 2011. Upon applying the method of video analysis and comparing the results of the two contests, we have noted the increase of the gymnasts' scores, as shown by the values of the Student "t" test, where we note a significance threshold of p<0.001. By interpreting the results, we can assert that the application of this method led to the gymnasts' awareness of their own technical value and to achieving remarkable results in competitions.